Adaptasi Ajaran Tasawuf di Jawa: Perspektif Personal dan Kultural - Wiwi Siti Syajaroh (JURNAL INDO-ISLAMIKA, 2017)
This paper studies the mystical tenets [of Islam ( tasawwuf )] as essentially inward aspects that enlive all traditional Javanese culture. Here, this article uncovers that these mystical teachings of Islam are rooted in the culture of the Javanese Priyayi. Moreove, this article finds that a number of sects of Javanism (kebatinan/kepercayaan ) is a insurgence of Javanism. Here, this article detects that the main teaching of Javanism is the belief that human beings is able to have relationship with God by meditation. In this respect, this paper argues that historically the tasawwuf was able to spread Java because of the psychological and cultural factors that took place a long time ago in the region.